Computer aided analysis of nonlinear systems - Ye, Li Li. (2008)
This dissertation focuses on the automated phase portrait plotting in the computer-aided analysis of nonlinear systems that are described by second order ordinary differential equations. The program was developed using MATLAB and it automatically plots the phase curves in the phase plane.